Organization of inclusive education for schoolchildren with special needs in modern school practice - Verovkina, Zhanna; Martsinovska, Iryna; Vasylieva , Halyna; Savinova, Natalia; Chopyk , Lesia (Revista Eduweb, 2023)
In the article, the features of the organization of the educational process for pupils with special needs, the involvement of a wide range of educational services to improve academic achievement, and the development of the child’s personality are considered. The article aims to identify the content, main criteria, and algorithms for organizing inclusive education for pupils with special needs. The attitudes of parents, educators, and social workers to the proposed system of inclusive education are revealed. The result of the work is an algorithm for introducing inclusive education, determining its effectiveness, and a positive assessment of the system’s effectiveness by parents, social workers, and educators (11%, 13%, and 15%, respectively). In this context, it is promising to research and design specific examples of the organization of inclusive education management systems.